Broad-spectrum antiviral agents: secreted phospholipase A2 targets viral envelope lipid bilayers derived from the endoplasmic reticulum membrane. Issue 1 (December 2017) - Chen, Ming; Aoki-Utsubo, Chie; Kameoka, Masanori; Deng, Lin; Terada, Yutaka; Kamitani, Wataru; Sato, Kei; Koyanagi, Yoshio; Hijikata, Makoto; Shindo, Keiko; Noda, Takeshi; Kohara, Michinori; et al.
Abstract Hepatitis C virus (HCV), dengue virus (DENV) and Japanese encephalitis virus (JEV) belong to the familyFlaviviridae . Their viral particles have the envelope composed of viral proteins and a lipid bilayer acquired from budding through the endoplasmic reticulum (ER). The phospholipid content of the ER membrane differs from that of the plasma membrane (PM). The phospholipase A2 (PLA2 ) superfamily consists of a large number of members that specifically catalyse the hydrolysis of phospholipids at a particular position. Here we show that the CM-II isoform of secreted PLA2 obtained fromNaja mossambica mossambica snake venom (CM-II-sPLA2 ) possesses potent virucidal (neutralising) activity against HCV, DENV and JEV, with 50% inhibitory concentrations (IC50 ) of 0.036, 0.31 and 1.34 ng/ml, respectively. In contrast, the IC50 values of CM-II-sPLA2 against viruses that bud through the PM (Sindbis virus, influenza virus and Sendai virus) ortrans -Golgi network (TGN) (herpes simplex virus) were >10, 000 ng/ml. Moreover, the 50% cytotoxic (CC50 ) and haemolytic (HC50 ) concentrations of CM-II-sPLA2 were >10, 000 ng/ml, implying that CM-II-sPLA2 did not significantly damage the PM. These results suggest that CM-II-sPLA2 and its derivatives are good candidates for the development of broad-spectrum antiviral drugs that target viral envelope lipid bilayers derived from the ER membrane.